EFEKTIFITAS MANAJEMEN PENDIDIKAN KARAKTER PADA SEKOLAH DASAR NEGERI 47 AMBON - Simon Saulinggi; Melisa Nur Asima Sidabutar (Jurnal Manajemen Pendidikan, 2013)
Problem of moral character happening now more numerous and complex than ever before. Government efforts to incorporate eharacter educationin schools by making the head of the Research and Development of Educationand the Maluku provincial government through the Department ofEducation, Youth and Sports Affairs to determine SD 47 Ambonas the only elementary schoolin thecity of Ambon to implement the National Character Education and Culture. This is what lies behind the author to examine the level of Character Education Management Effectiveness at the Elementary School 47 Ambon. This research aims to find out how Management Character Education, is clone what Implementation Strategy is used and determine the level ofeffectiveness of the Character Educationin Elementary School 47 Ambon. Study used a descriptive approach with qualitative methods, which are based on the conditions and the context of the problem being studied. The sampling technique was purposive sampling, with a total sample of 11 people consisting of the Head of School, Character Education Team Leader, Supervisor School, School Committee, Students Parents, and Students. Data collection techniques used were non participant observation, semi-structured interviews, and documentation.While the data analysis done by: data reduction, Presentation of data (display data), With drawal Conclusions and Verification (conclusion drawing/verivication). The results showed that the Character Education Management Effectiveness at Elementary School 47 Ambonassessed Start Evolving (MB), which the participants have started to show signs of behavior that is expressed in the indicator and begin consistent, because in addition to the existing understanding and awareness, also received reinforcement immediate environment also the wider environment. Evaluation of the character education management programmed, implemented, monitored and evaluated for further action, showed a change or an increase inbehavior/characterof the school community from the time before the implementation of character education. Principals, educators and education and trying to get used to exemplify the increasingly well to modeled because they understand that the child will continue to do what it sees what it means and the teachers do not keep on doing what the teachers aid. Teachers conduct on going assessment, as teachers in the classroom or outside the classroom trough an ecdotal records when looking at the behavior with respect to the value which is developed. Keywords: Character Education Management, Strategy and Effectiveness of Character,Education.